Comparison of different developmental stages of jujube (Ziziphus jujuba) fruit and identification of Hub genes - Li Yalan; Ren Tian; Qu Siyu; Hao Qing; Fan Dingyu; Alimire Alimu (Folia Horticulturae)
Ziziphus jujuba is one of the oldest cultivated and economically important nut trees and its development and ripening processes involve numerous physiological and biochemical changes. This study conducted a fruit transcriptomic analysis during the fruit expanding (FE) stage, white-mature (WM) stage, early red (ER) stage and full red (FR) stage. The expression of mRNAs was then compared at four different stages. Subsequently, functional enrichment analysis was performed on the differentially expressed genes (DEGs) identified in each group. The relationships among DEGs within each group were assessed and hub genes were identified using the degree algorithm of Cytohubba. Finally, the expression levels of these hub genes were compared across the four stages. Based on the results, a total of 3448 unannotated novel genes were identified. The number of DEGs in the four group comparisons WM vs FE, ER vs WM, FR vs ER and FR vs FE groups were 1576, 8561, 1073 and 7884 DEGs, respectively, and mainly involved in biological processes such as stimulation, defence, immunity, ADP binding, DNA-binding transcription factor activity, secondary active transmembrane transporter activity, etc. In total, 20 hub genes were gained. The expression of 4 hub genes was not significantly different among four stages, namely LOC107409707, LOC107416546, LOC107415777 and LOC107414679, and the expression of the remaining hub genes was markedly different. Our study provides a transcriptional level reference to reveal further the dynamic developmental process of winter jujube fruits and a theoretical basis for improving the quality of winter jujube fruits.